(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
Risk analysis is made in several fields of science, moreover in business, manufacturing, protection of enviroment, disaster recovery, hygiene, labour safety, or in the increasingly important information security. Laws and standards control the risk assessement in many cases, however they don’t contain any guide for the execution. The aim of this article is to highlight some well-defined risk analysis methods in my article and shortly present the possible adaptations thereof. In case of different processes the most difficult task is to adjust the processes to the problems in a way, which enables to minimize deviations and faults resulting from men’s subjective judgement. Both qualitative and quantitative processes are contained the methods, and advantages, disadvantages, application possibilities thereof in details are presented.